2008
DOI: 10.1016/j.jmb.2008.02.066
|View full text |Cite
|
Sign up to set email alerts
|

A Cell-penetrating Helical Peptide as a Potential HIV-1 Inhibitor

Abstract: The capsid domain of the human immunodeficiency virus type 1 (HIV-1) Gag polyprotein is a critical determinant of virus assembly, and is therefore a potential target for developing drugs for AIDS therapy. Recently, a 12-mer alpha-helical peptide (CAI) was reported to disrupt immature- and mature-like capsid particle assembly in vitro; however, it failed to inhibit HIV-1 in cell culture due to its inability to penetrate cells. The same group reported the X-ray crystal structure of CAI in complex with the C-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
247
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(257 citation statements)
references
References 47 publications
9
247
0
1
Order By: Relevance
“…For such cases, the stabilization of peptides as pre-formed helices through stapling with hydrocarbon chains reduces the entropic penalty that a random coil peptide has to pay as it adopts a helical fold for binding; this method has so far been very successful. [47][48][49][50][51] MD simulations were carried out for a set of such peptides that were designed to bind to MDM2. 53 We find that the good binders assume helicity in solution as has also been demonstrated in other simulation studies 53,54 and now we also show that they assume extended helicity when bound to MDM2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For such cases, the stabilization of peptides as pre-formed helices through stapling with hydrocarbon chains reduces the entropic penalty that a random coil peptide has to pay as it adopts a helical fold for binding; this method has so far been very successful. [47][48][49][50][51] MD simulations were carried out for a set of such peptides that were designed to bind to MDM2. 53 We find that the good binders assume helicity in solution as has also been demonstrated in other simulation studies 53,54 and now we also show that they assume extended helicity when bound to MDM2.…”
Section: Discussionmentioning
confidence: 99%
“…However, clearly the physico-chemical parameters that contribute to the outcome are far more complex as has been demonstrated for the NMR structure of the monomeric C-terminal domain of HIV-1 capsid bound to inhibiting staples; in this case, the staples are far from the surface that is being targeted. 50,51 Clearly much more needs to be discovered to understand the structure-energy-functions of these exciting molecules. Our simulations have provided insights …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MR contrast media are useful in evaluating the efficacy of therapy by allowing the determination of tissue perfusion, blood volume, vascular permeability, angiogenesis and cellular integrity [21,22] . For example, after effective chemotherapy there is a decrease in the size of the lesion and number of microvessels, which can be detected on contrast enhanced MR images.…”
Section: Time (Figures 2 and 3)mentioning
confidence: 99%
“…Saeed et al [21] demonstrated the advantageous effects of vascular endothelial growth factor and hepatocyte growth factor genes, delivered transendocardially under MR-guidance, in creating new blood vessels and reducing the size of infarcted myocardium using gadolinium-based MR contrast media [22] . Others used contrast enhanced MRI for determining the effects of intracoronary stem cell therapy on left ventricular function [88] .…”
Section: Future Perspectivesmentioning
confidence: 99%